Systematic review of emerging trends in soil-based probiotic - Leong, Sui Sien; Korel, Figen; Khairul, S. R.; Lingoh, A. D.; Toh, Seng Chiew (Malaysian Society of Soil Science, 2024)
Soil-based probiotics (SBPs) are microorganisms originating from soil that have the potential to significantly enhance soil fertility and plant health, similar to the benefits of conventional probiotics in human and animal health. While much is known about the role of SBPs in the animal’s gut, the specific mechanisms and long-term impacts of SBPs in soil ecosystems remain underexplored. This review systematically summarizes recent research on SBPs, with a focus on lactic acid bacteria (LAB), including Lactobacillus and Bifidobacterium, and their role in soil and plant ecosystems. A comprehensive literature search was conducted using major databases, including PubMed, Web of Science, Scopus, and Google Scholar, covering the past 20 years. Out of 90 initial studies, 30 were excluded for irrelevance, and a further 60 were omitted based on selection criteria, leaving only the most relevant studies for analysis. The review highlights the multifaceted applications of SBPs in agriculture, focusing on their ability to enrich soil microbiomes, promote plant growth, and suppress pathogens. Additionally, SBPs offer sustainable alternatives in livestock feed. A comparison between SBPs and traditional probiotics underscores the unique advantages of soil-derived strains in agricultural systems. As sustainable agriculture practices grow in importance, SBPs present a natural, eco-friendly approach to improving soil health and plant resilience. Continued research is vital to fully harness the potential of SBPs, contributing to long-term soil health, sustainable farming, and global food security.